Priorities in health - Jamison, Dean T. (World Bank WashingtonUS, 2006)
This is the companion volume to the second edition of Disease control priorities in developing countries (DCP2). Highlights DCP's main messages, principal methods of analysis, and looks at the scope of diseases and issues covered. Enables access to the massive amount of information and analysis contained in DCP2.